The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1136/bmjopen-2016-011975
|View full text |Cite
|
Sign up to set email alerts
|

Electronic capture of patient-reported and clinician-reported outcome measures in an elective orthopaedic setting: a retrospective cohort analysis

Abstract: ObjectivesTo determine whether an entirely electronic system can be used to capture both patient-reported outcomes (electronic Patient-Reported Outcome Measures, ePROMs) as well as clinician-validated diagnostic and complexity data in an elective surgical orthopaedic outpatient setting. To examine patients' experience of this system and factors impacting their experience.DesignRetrospective analysis of prospectively collected data.SettingSingle centre series. Outpatient clinics at an elective foot and ankle un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…As other studies have found, there is a need for organisations to invest in electronic systems [ 44 ]. However, this may not always be feasible, for example due to budget constraints or a lack of prioritisation by the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…As other studies have found, there is a need for organisations to invest in electronic systems [ 44 ]. However, this may not always be feasible, for example due to budget constraints or a lack of prioritisation by the organisation.…”
Section: Discussionmentioning
confidence: 99%
“…the National Health Service England PROMs programme costs £825 000 annually [48]. Malhotra et al demonstrated electronic PROMs (ePROMs) can be successfully implemented into a service and innovative data collection methods improve the ease of administration, data capture rates and lower costs [49]. The implementation of ePROMs is now a realistic goal as the majority of patients now have access to smart-phones, tablet devices and internet access; alongside developments in electronic databases, which enable real-time collection of data.…”
Section: Discussionmentioning
confidence: 99%
“…Deprivation and increased age are known to be associated with lower use of the internet, and a 2013 study finding indicated that younger, more affluent patients were more likely to use an electronic PROMs system (Ashley et al). Despite this, electronic collection of patient reported data has been carried out successfully in the UK (Malhotra et al 2016). Electronic data capture is less costly than traditional paper based methods and removes the need for data entry.…”
Section: Strengths and Weaknessesmentioning
confidence: 99%